Health literacy: A consensus group on Greek terminology - Efthymiou, Areti; Menikou, Ioanna; Middleton, Nicos; Kondilis, Barbara K.; Papastavrou, Evridiki (My University, 2021)
Health literacy has become an important research field in public health and health care. People with low levels of health literacy utilize more health services, visit emergency rooms more frequently, have longer hospital stays, and are less likely to adhere to treatment plans. In Greece and Cyprus, research on this topic has become popular only in the last decade, in comparison with the United States of America (USA), the United Kingdom (UK), Australia, and China. A core issue in the Greek language is the use of common terminology in medical research. For this reason, a consensus group was organized to validate the work of the Greek team participating in the Health Literacy Survey in Europe (HLS-EU) concerning the terminology of health literacy. The consensus group will suggest a common means of assessment in Greece and Cyprus, and discuss future research and the role of all the relevant stakeholders in health literacy interventions and dissemination of the common Greek terminology.
Εγγραμματοσύνη σε θέματα υγείας Ομάδα σύγκλισης απόψεων για την ορολογία
Keywords: Health literacy; Health promotion; Prevention; Qualitative research; Terminology